COTTON+SESAME- A DOUBLE STORY CROP PRODUCTION CASE STUDY - Khan, Muhammad Bismillah; Khaliq, Abdul (Journal of Research (Science), 2004)
An experiment was conducted at Agronomic Research Area, University of Agriculture, Faisalabad (Pakistan) with the objective of developing new planting patterns and multiple cropping techniques. Cotton was planted in two different patterns i.e. 80-cm spaced single rows (P1) and 120-cm spaced 2-row strips (40/120 cm) (P2). Sesame was grown as intercrop in the cotton as well as sole crop (P3). Sesame intercropped in 120 cm apart double row strips of cotton produced significantly greater number of capsules plant-1, higher economic and biological yields than those produced by sesame intercropped in 80 cm spaced single rows of cotton. However, planting density, plant height, seeds plant-1 and 1000-seed weight, were not affected by different planting patterns under study. In intercropping systems, cotton appeared to be dominated as it had lower value for relative crowding coefficient (k) and competitive ratio than the intercrop. Aggressivity value was the minimum for cotton+sesame in both the planting patterns which indicated that sesame was very competitive crop to cotton.